Interaksi Hukum Dalam Nilai Nilai Sosial - Robiyanto, Gustiawan; Rizka, M. Faisol; Angkasa, Nitaria (Universitas Muhammadiyah Metro, 2024)
Indonesia, with its cultural and social diversity, is a complex stage for the interaction between law and socio-cultural values. This paper aims to outline the role and impact of law-changing aspects in the socio-cultural context of Indonesia.Through a literature review, it is found that law often not only reflects cultural values, but can also be a significant agent of change in modernizing and adjusting the socio-cultural order. Factors such as globalization, information technology, and urbanization have shaped a dynamic legal landscape, presenting new challenges in maintaining a balance between cultural norms and legal advancement. Meanwhile, conflicts between local traditions and national or international law often create tensions in the Indonesian legal system. Nevertheless, through mechanisms such as inclusive legal interpretation and intercultural dialogue, efforts have been made to facilitate integration between legal and socio-cultural aspects. This research also highlights the need for a culturally sensitive approach in the law-making process, as well as the importance of community inclusion in policy formulation to achieve harmony between legal progress and cultural sustainability. By understanding these complex dynamics, it is hoped that the Indonesian people can develop a legal system that respects and strengthens their cultural heritage, while still adapting to the ongoing changes of the times